Temperature dependence of the surface plasmon resonance in silver nanoparticles - Yeshchenko, O.A.; Bondarchuk, I.S.; Alexeenko, A.A.; Kotko, A.V. (Functional Materials, 2013)
The temperature dependences of energy and width of the surface plasmon resonance were studied for silver nanoparticles with sizes 24 nm and 60 nm in silica host matrix in the temperature range of 17—700° C. The temperature increase leads to red shift and broadening of the surface plasmon resonance in Ag nanoparticles. The obtained temperature dependences were analyzed within the framework of theoretical model considering the thermal expansion of a nanoparticle, the electron-phonon scattering in the nanoparticle and the temperature dependence of dielectric permittivity of the host matrix. The thermal expansion was shown to be the main mechanism responsible for the temperature induced red shift of the surface plasmon resonance in silver nanoparticles. Meanwhile, the increase of electron-phonon scattering rate with increasing temperature was shown to be the dominant mechanism of the surface plasmon resonance broadening in the silver nanoparticles.